Case Report: ECMO-Assisted Uniportal Thoracoscopic Tracheal Tumor Resection and Tracheoplasty: A New Breakthrough Method - Li, Zi-Hao; Dong, Bo; Wu, Chun-Li; Li, Shi-Hao; Wu, Bin; Sheng, Yin-Liang; Li, Feng; Qi, Yu (Frontiers in Surgery, 2022)
Primary tracheal tumors are seldom seen, and most of them are malignant. At present, the main treatment is surgical resection. It is rare to accomplish tracheal tumor resection and tracheoplasty with single-port thoracoscopic. In order both to maintain the patient's oxygen supply during surgery and to miniaturize the surgical incision, we have innovatively integrated the ECMO-assisted and single-port thoracoscopic techniques for the first time, perfectly achieving tracheal tumor resection and tracheoplasty. The intraoperative manipulation was only 180 minutes in duration. The patient returned to the intensive care unit and recovered smoothly after the surgery. The patient was discharged from the hospital seventeen days after the operation. ECMO-assisted single-port thoracoscopic tracheal resection and tracheoplasty provides a new idea and method for colleagues.